Design of people movement trackers application in determining public transportation corridors for sustainable smart city transportation systems - Syarifuddin, Rizal; Purnomo, Hari; Mansur, Agus; Cahyo, Winda Nur (Edelweiss Applied Science and Technology, 2025)
The development of a sustainable smart city transportation system in Makassar requires accurate data on people’s movement patterns to support the effective planning of public transportation corridors. This study aims to design a people movement tracker application as a data-driven tool for public transport route planning. The application was developed using the Waterfall software development method, which includes the stages of requirement analysis, system design, implementation, testing, and maintenance. The application integrates GPS tracking, user behavior analysis, and spatial data processing. A total of 23 participants who installed the application provided training data on their mobility within Makassar. The results show that real-time mobility tracking can effectively identify movement patterns and areas with high population density, which can be used to determine more responsive public transportation corridors. The application offers practical contributions to transport policy and infrastructure planning based on actual user needs. This study concludes that combining a structured software engineering approach with digital mobility tracking technology is essential for building a sustainable and adaptive urban mobility system in the era of smart cities.